Pathogenetic characteristics of infectious diarrhea in Yantai City, Shandong Province, 2018-2019 - Qiao Gao; Hong Liu; Weixia Yu; Zhaolin Wang; Ying Yang; Kai Guo; Zhenlu Sun (Frontiers Media S.A., 2023)
BackgroundAnalysis of the pathogenic spectrum, epidemiological characteristics and molecular epidemiological features of important pathogens of infectious diarrhea in Yantai City, Shandong Province, 2018-2019, were analyzed to provide a reference basis for the prevention and control of infectious diarrhea.MethodsA total of 1514 stool specimens were collected within 3 days of the onset of diarrhea in secondary or higher hospitals in Yantai from 2018-2019, and all specimens were tested for the presence of seven major viruses and three major bacteria by employing reverse transcription ploymeraer chain reaction (RT-PCR). Population and seasonal analyses were also performed on positive samples for infectious diarrhea. The top two ranked rotavirus and norovirus were focused on genotyping and analysis of geographical distribution.ResultsThe study showed that the high prevalence of infectious diarrhea in Yantai, Shandong Province, for two consecutive years in 2018 and 2019 was in young children aged 1-5 years, accounting for 48.6% of the total number of cases. Viral diarrhea was distributed throughout the year with no obvious seasonal distribution, while bacterial diarrhea was predominant in summer. Of 1514 stool specimens, the total positive rate of specimens was 43.92% (665/1514). One pathogen was detected in 507 specimens, two pathogens in 107 specimens, and three pathogens in 44 specimens, with mixed infections accounting for 22.71% of positive specimens (151/665). Viral diarrheal pathogens accounted for 93.23% (620/665) of positive samples. The percentages of positive samples for Rotavirus (RV), Norovirus GI, Norovirus GII, Enterovirus universal (EV), Enteroadenovirus (EAdV), Sapovirus (SaV), Astrovirus (Astv), Salmonella (SE), Listeria monocytogenes (LiMo), and Vibrio parahaemolyticus (VP) were 48.57%, 3.61%, 15.34%, and 10.68% of the total positive samples.ConclusionsThis study analyzed in detail the composition of infectious diarrhea pathogen spectrum, pathogen alternation pattern, seasonal distribution and population distribution of pathogens in Yantai City, Shandong Province, 2018-2019, to provide a basis for improving relevant local preventive measures and reducing the disease burden.